Effect of Teucrium polium L Extract on Growth of E.coli in Liquid Media and Effect on Growth in Poisoned Food Technique - mohammed, Iqbal Harbi; Fathi, Shams Munaf; Kadhum, Rafed Abbas; Marhoon, Abeer Ali (Medical Science Journal for Advance Research, 2024)
Background: Escherichia coli is a facultative anaerobic Gram-negative bacterium from the Enterobacteriaceae family that colonizes the gastrointestinal tract. Teucrium polium L is a medicinal plant growing in the western Mediterranean region. Different studies aim to determining the stages at which E. coli growthsis more sensitivity to certain concentrations of medicinal plant like Alcoholic and aqueous extract of Teucrium polium and their effective concentration based on the zone of inhibitions on plate that previously inoculate with Escherichia coli and the plant extracts and utilized to monitor growth of bacteria. in present study it was indicated that Teucrium polium L ethanolic and aqueous extracts was showed a significant outcome in inhibition of this bacteria. Conclusion: In different infection the role of E.coli is very important subjects, in present study it was indicated that Teucrium polium L ethanolic and aqueous extracts was showed a significant outcomes in inhibition of this bacteria, these data may be aid in discovering of new remedies from natural sources.